Search
Ask a question
0

Inverse Function

f(x)=6x-1


Not sure on where to start from...

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Tamara J. | Math Tutoring - Algebra and Calculus (all levels)Math Tutoring - Algebra and Calculus (al...
4.9 4.9 (51 lesson ratings) (51)
0

Given     f(x) = 6x -1 ,     find      f-1(x)     

First, let   f(x) = y

     y = 6x - 1

Replace every x with y and every y with x:

     x = 6y - 1

Solving this equation for y given you the inverse of the original function f(x):

     x + 1 = 6y - 1 + 1

     x + 1 = 6y

     (x + 1)/6 = (6y)/6

     (x + 1)/6 = y

Thus,

          f-1(x) = (x + 1)/6